Dashboard Penerimaan Mahasiswa Baru Unhasy Dengan Algoritma Naïve Bayes Classifier - Ali, Mahrus (Inovate, 2021)
Every university certainly expects the number of new student admissions (NSA) to always increase every year to improve the quality of the university. However, does the university carry out an analysis related to the input of new student admissions according to the classification. According to the results of research and research studies conducted by interviewing the new student admissions committee at Hasyim Asy'ari Tebuireng University, Jombang. Whereas every year there has not been a system created for classifying new students based on school origin, student address, school or madrasah level and achievement. Because the classification of this data is used as the main data to analyze the condition of new students who are accepted and used as material for evaluating the new student admissions committee (NSA) and determine strategies for recruiting new students the following year. effective way of clustering technique. The interface is built in the form of a web-based dashboard so that it can be accessed online on the campus intranet and can also be used as the main data for evaluating new student committees at Hasyim Asy'ari Tebuireng University Jombang. Keywords: Algoritma naïve bayes classifier, dashboard.